Equilíbrio líquido-líquido em sistema aquoso bifásico formado por [Bmim]BF4 + MgSO4 + água em diferentes temperaturas - Silva, Michele Dorcília De Oliveira (2019)
The aim of the present work was to obtain and characterize aqueous two-phase systems (ATPSs) formed by the mixture of 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim]BF4) + magnesium sulfate (MgSO4) + water at 278.15; 288.15; 298.15; 308.15 and 318.15 K. The effect of the mixture composition, temperature and cation on the phase behaviour were evaluated in this work. It was observed experimentally that at lower temperatures the process of separation of the phases in these ATPSs is favoured, characteristic of an exothermic process and also that the decrease of temperature leads to the occurrence of phase inversion in these systems. Another aspect evaluated was the extent of the exchange of the ionic pairs in the various phase equilibria evaluated at different mixture compositions and temperature. The quantitative analyzes of the species involved in the liquid-liquid equilibrium in each phase showed that no significant changes of the original ionic pairs occur. The ability of magnesium sulfate and magnesium cation to induce the phase separation compared to the behaviour of other similar ATPSs formed by sulfate salts containing different cations.